Opportunities and barriers to involving persons with health limitations and disabilities in physical education and sports - Minina V.N.; Ivanov S.A.; Panevina M.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the factors that promote and hinder the involvement of people with health limitations (disabilities) in systematic physical education and sports. Methods and structure of the study. An all-Russian sample survey was conducted: of the population with health limitations, aged from 18 to 80 years and older (604 respondents with health limitations, including disabilities, of which: 22.2% with the first disability group, 31.5 % - second, and 38.2% - third, there is no disability, but 8.1% of respondents have health restrictions); survey of coaches and instructors working in the field of adaptive sports: sports of the deaf, sports of the blind, sports of the LMS (persons with lesions of the musculoskeletal system), sports of PID (persons with intellectual disabilities) (323 experts, among whom 67.8% have work experience in adaptive sport for over five years). The online survey was conducted using specially designed questionnaires. More than half (58.2%) of the surveyed coaches and instructors work with both adults and children. The categories of disabled people with whom coaches and instructors work include persons with the following types of nosologies: musculoskeletal disorders (65.3%), hearing impairment (41.8%), visual impairment (25.7%), mental disorders (35.6%). Results and conclusions. It has been established that a significant number of people with disabilities (disabilities) are aware of the importance of physical activity for maintaining and strengthening health, for improving psychological well-being and more successful socialization, and they are actively involved in physical education and sports. Three groups of barriers have been identified that impede the involvement of this category of the population in the field of physical education and sports: individual barriers; barriers related to the availability of physical culture and sports infrastructure; barriers caused by dissatisfaction with existing conditions for physical activity.